Micro- and meso-level governance institutional interface in community development : the case of Sinyala community forest resource management in Malawi. - Jana, Michael Patrick Eliezer (My University, 2009)
The introduction of democracy in many sub-Saharan African countries in the early 1990s ushered in a new local governance perspective that is hinged on decentralization, emphasizing people-centred and participatory approaches within the Humanist development paradigm. At community level, the implementation of this development approach posed a challenge of synergizing enduring indigenous local governance institutions and the formal institutions. Using the case of Sinyala community forest management in rural Malawi, the paper argues that the introduction of decentralized community based forest management in Sinyala was undermined seriously because it did not adequately engage with and incorporate indigenous community governance institutions and community members’ expectations. As a result, there have been institutional incompatibilities and discontinuities hence disequilibrium between the formal and indigenous local institutions. The paper also shows that community development activities, including the community based forest management, are not properly synergized in Sinyala community because of disjointed initiatives by formal meso-level actors. Given the exogenous nature of the decentralized community based forest management regime, much as its introduction was participatory, the paper notes the increasing levels of dependency and need for incentives in participation among community members in community forest management and indeed many community development activities. To improve community collective action and development within a decentralized framework therefore, this research paper argues that community development efforts need to engage with and build on existing indigenous institutions, provide relevant and appropriate incentives to boost community participation, build and strengthen cross-community governance institutions where a common property resource overlaps two or more communities, and implement a coherent community development policy that will synergize community development efforts from different actors at all levels of governance.